Novel role of estrogen receptor-α on regulating chondrocyte phenotype and response to mechanical loading. Issue 2 (February 2022) - Wang, N.; Zhang, X.; Rothrauff, B.B.; Fritch, M.R.; Chang, A.; He, Y.; Yeung, M.; Liu, S.; Lipa, K.E.; Lei, G.; Alexander, P.G.; Lin, H.
Summary: Objective: In knee cartilage from patients with osteoarthritis (OA), both preserved cartilage and damaged cartilage are observed. In this study, we aim to compare preserved with damaged cartilage to identify the molecule(s) that may be responsible for the mechanical loading-induced differences within cartilage degradation. Methods: Preserved and damaged cartilage were harvested from the same OA knee joint. RNA Sequencing was performed to examine the transcriptomic differences between preserved and damaged cartilage cells. Estrogen receptor-α (ERα) was identified, and its function of was tested through gene knockin and knockout. The role of ERα in mediating chondrocyte response to mechanical loading was examined via compression of chondrocyte-laded hydrogel in a strain-controlled manner. Findings from the studies on human samples were verified in animal models. Results: Level of estrogen receptor α (ERα) was significantly reduced in damaged cartilage compared to preserved cartilage, which were observed in both human and mice samples. Knockdown of ESR1, the gene encoding ERα, resulted in an upregulation of senescence- and OA-relevant markers in chondrocytes. Conversely, knockin of ESR1 partially reversed the osteoarthritic and senescent phenotype of OA chondrocytes. Using a three-dimensional (3D) culture model, we demonstrated that mechanical overload significantly suppressed ERα level in chondrocytes with concomitant upregulation of osteoarthritic phenotype. When ESR1 expression was suppressed, mechanical loading enhanced hypertrophic and osteogenic transition. Conclusion: Our study demonstrates a new estrogen-independent role of ERα in mediating chondrocyte phenotype and its response to mechanical loading, and suggests that enhancing ERα level may represent a new method to treat osteoarthritis.